If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15xsquared + 9x = 0 Solving 15adeqrsux + 9x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9x' to each side of the equation. 15adeqrsux + 9x + -9x = 0 + -9x Combine like terms: 9x + -9x = 0 15adeqrsux + 0 = 0 + -9x 15adeqrsux = 0 + -9x Remove the zero: 15adeqrsux = -9x Divide each side by '15deqrsux'. a = -0.6d-1e-1q-1r-1s-1u-1 Simplifying a = -0.6d-1e-1q-1r-1s-1u-1
| x^2+8-8=0 | | 3(x+4)=5x+6 | | 8x^4+10x^3+9x^2+x-1=0 | | 7x-10=3x+26 | | 10x-6 = 114 | | 1+2n-3=74 | | 15x+77=77 | | 7.19m/2 | | 4x+30+2x+15=90 | | 28=2b/5-2 | | (5x-14)=(3x+4) | | 4x=10x+5 | | 2x+15=4x+30 | | 4x+1=2(x+7) | | -11=m+1+2n | | 3z+5+7z-5=90 | | 8a-5=27 | | 12y/4-8=33 | | 2(a-2)=5(9-a) | | 50h+20= | | x^2+10x=-12 | | 6x-8=1/2(6x | | 14f+21= | | 5/7*-13=26 | | (a+16)(a-18)=180 | | 3(x-7)=24-9x | | 2(2x-1)=2(x+2) | | -4+-1= | | 5y+18=43 | | 4a-3*2=-4 | | 12w-36= | | y+18=47 |